2021
DOI: 10.21037/atm-21-2374
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prediction model for the risk of recurrent laryngeal nerve lymph node metastasis in thoracolaparoscopic esophagectomy with cervical anastomosis

Abstract: Background: There are no effective preoperative diagnostic measures to predict the probability of left and right recurrent laryngeal nerve (RLN) lymph node (LN) metastasis using preoperative clinical data in patients undergoing thoracolaparoscopic esophagectomy with cervical anastomosis. Methods:We retrospectively reviewed the clinical data of 1,660 consecutive patients with thoracic esophageal cancer who underwent esophagectomy with cervical anastomosis at the Department of Thoracic Surgery at the First Affil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The recurrent laryngeal nerve (RLN) lymph nodes (LNs) are the crucial indicator during esophagectomy, which may decide the necessity of cervical lymphadenectomy in some previous studies ( 4 , 5 ). The RLN LNM in patients with ESCC is frequently observed at a rate of 18–63% in the previous studies ( 6 13 ). Routine esophagectomy with three-field lymph node resection for all ESCC patients is still controversial due to the balance of complication and survival ( 9 , 14 ).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The recurrent laryngeal nerve (RLN) lymph nodes (LNs) are the crucial indicator during esophagectomy, which may decide the necessity of cervical lymphadenectomy in some previous studies ( 4 , 5 ). The RLN LNM in patients with ESCC is frequently observed at a rate of 18–63% in the previous studies ( 6 13 ). Routine esophagectomy with three-field lymph node resection for all ESCC patients is still controversial due to the balance of complication and survival ( 9 , 14 ).…”
Section: Introductionmentioning
confidence: 77%
“…In CT images, a diameter of RLN LNM could reflect the status of RLN LNM and short diameter RLN LNs greater than 10 mm are usually judged as metastasis. However, previous studies demonstrated that the cut-off of the short diameter of RLN LNs to diagnose metastasis was shorter than 10 mm, like 6.5 mm ( 19 ) and 7.5 mm ( 6 ). Additionally, it is well-known that using a CT image to distinguish benign inflammation of LNs from malignant metastasis and to diagnose metastasis in LNs less than 5 mm is difficult.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies reported that the sensitivity of CT evaluation was 30–64.7% [ 39 , 40 ]. MRI has a better performance in discriminating benign or malignant LNs, but it is a relatively expensive and time-consuming procedure [ 41 ]. PET/CT could provide additional metabolic and functional information, but it still remained controversial in evaluating cervical LN status in ESCC [ 42 ].…”
Section: Discussionmentioning
confidence: 99%